Development of a PrGO-Modified electrode for uric acid determination in the presence of ascorbic acid by an electrochemical technique - Tukimin, Nurulkhalilah; Abdullah, Jaafar; Sulaiman, Yusran (Multidisciplinary Digital Publishing Institute, 2017)
An attractive electrochemical sensor of poly(3,4-ethylenedioxythiophene)/reduced graphene oxide electrode (PrGO) was developed for an electrochemical technique for uric acid (UA) detection in the presence of ascorbic acid (AA). PrGO composite film showed an improved electrocatalytic activity towards UA oxidation in pH 6.0 (0.1 M PBS). The PrGO composite exhibited a high current signal and low charge transfer resistance (Rct) compared to a reduced graphene oxide (rGO) electrode or a bare glassy carbon electrode (GCE). The limit of detection and sensitivity of PrGO for the detection of UA are 0.19 μM (S/N = 3) and 0.01 μA/μM, respectively, in the range of 1–300 μM of UA.